Application of microsatellite fingerprints for pedigree analysis of Hungaricum grapevine varieties - Galbács, Zsuzsanna; Molnár, Stella; Halász, Gábor; Hoffmann, Sarolta; Veres, Anikó; Galli, Zsolt; Szőke, Antal; Tóth, Zsófia; Pilinszky, Katalin; Wichmann, Barnabás; Kozma, Pál; Kiss, Erzsébet; et al. (Acta Agraria Debreceniensis, 2007)
the Carpathian Basin were involved into our examination, which aimed at genotyping their accessions. DNA fingerprints of 101 varieties were determined with 6 microsatellite markers till 2005, resulting in successful discrimination of the accessions. Based on these results for pedigree determination, even more cultivars and primers were involved into the analyses. For studying the origin of Csabagyöngye and for proving the parent-progeny relations of Irsai Olivér and Mátrai muskotály, 19 microsatellite markers were applied, while 11 were selected for tracing the origin of Királyleányka. Genetic distances between the varieties were estimated with cluster analysis and demonstrated by dendrogram, proving that the varieties can be discriminated from each other based on the microsatellite allele sizes. Pedigree of Irsai Olivér and Mátrai muskotály has been confirmed by microsatellite allele size results, searching for the parents of Csabagyöngye and Királyleányka is in progress, since the molecular-marker based pedigree does not correspond with the putative origin of these cultivars. Our results excluded progeny-parent relationships in the Csabagyöngye-Bronnerstraube-Muscat ottonel (Ottonel muskotály) and the Királyleányka-Kövérszőlő combinations.